Studi hubungan antara penguasaan kosakata dan minat menulis dengan keterampilan menulis deskripsi pada peserta didik kelas V sekolah dasar - Dyah Adityaningrum; St Y Slamet; Tri Budiharto (Jurnal Pendidikan Dasar, 2021)
This study aims to 1) knowing whether there is a relationship between vocabulary mastery and description writing skills; 2) knowing there is a relationship between writing interest and description writing skills; 3) knowing whether there is a relationship between vocabulary mastery and writing interest together with descriptive writing skills. This research uses survey correlational study method. The population of this study were students of class V SD in Laweyan District, 2020/2021 academic year. Data collection techniques using tests and questionnaires. Based on the data analysis, it can be concluded that 1) there is a significant relationship between vocabulary mastery and the skill of writing descriptions of r count (0.72), the correlation coefficient was tested by t test, the results of tcount (10.36)> t table (1.66); 2) there is a significant relationship between writing interest and writing skills description r count (0.42), the correlation coefficient was tested by t test, the results of t count (4,63)> t table (1.66); 3) there is a significant relationship between vocabulary mastery and interest in writing along with descriptive writing skills ry12 of (0.85), the coefficient of significance with the F test is obtained Fcount = 136,47> Ftable = 3.09